ESTUDIO DE INOCUIDAD DE Salmonella enterica, SUBESPECIE enterica, SEROTIPO ENTERITIDIS, VAR. DANYSZ, LISINA NEGATIVA EN POLLOS PARRILLEROS - Rodríguez A., Natalia (2006)
The Salmonella enterica, serotipe Enteritidis, var Danysz, negative lysine is used as a component in a product for biological control of rodents. The present study evaluated the innocuosness of the strain in 120 1-day old Cobb Vantress broiler chicks of both sexes. They were divided into 3 groups: Group A was fed at 5, 6 and 7 days of age with a commercial broiler feed containing 20% of the rat poison, Group B received 1 ml containing 108 CFU of the bacteria in the crop at 8 days of age, and Group C was kept as a control group. Clinical signs, mortality, recovery of the experimental strain used from liver and spleen, body weight, and serological response were recorded. All birds were weighed every week. Two chicks were ramdomly selected and necropsied from each group on daily basis since the fifth day and for a week. Serum samples and selected tissues were collected for bacteriological culture. Additionally, serum samples were collected at day 21, 28, and 35 after challenge. The bacteriological and serological analysis were negative for Salmonella sp.; however, one bird on day 28 and 2 birds on day 35 after challenge from group A were positive in the agglutination test to Salmonella sp. In one of them, a Salmonella sp. positive lysine was isolated. Body weight differences among groups were not found by the seventh week.